IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK SELF-MANAGEMENT TERHADAP PERILAKU KECANDUAN MEDIA SOSIAL SISWA KELAS XII SMAN 1 MARGAASIH - Muhamad Iqbal Adhari; Nandang Rukanda; Tuti Alawiyah (IKIP Siliwangi, 2022)
This research is motivated by a phenomenon that occurs in SMA Negeri 1 Margaasih where some students experience social media addiction. As a from effort made to deal with these problems group guidance services with self-management techniques can be an alternative to reduce social media addiction behavior. Because it aims to make students able to determine the implementation of group guidance services with self-management techniques for students who are addicted to social media. The method used in this research is descriptive qualitative. The data collection instrument used observation, intervews and documentation. The subjects of this study amounted to 6 students who experienced addiction to social media can be reduced. So that the implementation of groups guidance services with self-management techniques is effective for class XII students of SMA Negeri Margaasih who are addicted to social media. Keywords: Group Guidance, Self-Management, Social Media Addiction